Peluang Titik Berat Otonomi Pada Daerah Provinsi dalam Sistem Ketatanegaraan Republik Indonesia - Fauzan, Muhammad (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2016)
This research entitled: Study Focus of Provincial Autonomy In the constitutional system of the Republic of Indonesia. The result of the research can be concluded that the First, the 1945 Constitution does not give a clear regulation about the options in the unit of local authority where the policy emphasis autonomy placed. The Second, in the history of the accomplishment regional administration, the policy emphasis on the autonomy at the regional Level II/regency/City normatively used to be implemented at the time of the validity of Law Number. 5 of 1974 and Law Number. 22 of 2004. The third, in the normative perspective chances of emphasis on provincial autonomy in the future is very open, it is because at the Article 18 of the 1945 amendments to the results of an open policy (open legal policy) about regional autonomy and regional autonomy center of gravity. In these provisions, do not regulate in which the emphasis regional autonomy placed. Thus the focus wisdom of regional autonomy is highly dependent on the political will of the legislators with regard to the situation of country, such as politics, security, economy and society when the law was made and the policy of the center gravity of regional autonomy in the Provincial or the Regency/City is not contradictory with the Constitution of Republic of Indonesia Year 1945.